ANALYZE THE URBAN ENERGY BALANCE OF DENSELY AREA JAKARTA USING SINGLE-LAYER URBAN CANOPY MODEL (Jurnal Teknologi (Sciences & Engineering), 2016)
Modification of surface and urban morphological changes, resulting in disruption of thermodynamic and dynamics properties in sub lowest layer of atmosphere, lead air temperature in downtown area higher than suburban. Study aims to analyze components of energy balance dense area of Jakarta using single-layer urban canopy model. H flux in solid area was dominant at noon. LE flux from dense area was very low Maximum intensity nocturnal heat island in dense areas was 2.5 °C. Higher value of h/w, S↓ received by wall and road decreases, causing H flux emitted by surface weakened. Instead L↑ emission trapped increases. The most dominant component that controls the balance of radiation and energy dense area are S↓ radiation, and H emission. Roof and road most active to respond heat during the day, and wall at night. Energy received or emitted by roof and road are greater than wall, due to shadowing effect. Surface temperature of urban areas is strongly influenced by local buildings configuration. Walls surfaces are less active emiting H at night for the h/w increasingly large. H emission from road surface decreases with increasing h/w. Increasing breadth of walls surfaces causing L↓ trapped in the canyon becomes higher, thus canyon temperatures remain high.